1999
DOI: 10.1089/jop.1999.15.413
|View full text |Cite
|
Sign up to set email alerts
|

Angiostatic Activity of Steroids in the Chick Embryo CAM and Rabbit Cornea Models of Neovascularization

Abstract: Ocular neovascular diseases represent a major cause of blindness in the world. Angiostatic steroids are a unique class of compounds which inhibit the formation of new blood vessels in various models, including ocular models of angiogenesis. In search of potent new anti-angiogenic agents for the treatment of ocular neovascular disease, a large group of steroids were evaluated for angiostatic activity in the chick embryo CAM model. Angiostatic activity was found among all steroid classes included in the study. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(24 citation statements)
references
References 21 publications
1
23
0
Order By: Relevance
“…Photodynamic therapy uses targeted laser activation of photosensitive dyes to selectively ablate or close choroidal vessels (SchmidtErfurth et al, 1999), and this therapy may soon be the standard of care for a limited group of ARMD patients. Small molecule inhibitors of angiogenesis are being developed to treat neovascular ARMD (Ishida et al, 1999;McNatt et al, 1999;Seo et al, 1999), and these may be useful for treating a larger population of patients in the future. The method of FITC-dextran labeling of CNV described in this study is reproducible and quanti®able, and it may accelerate the discovery of therapeutic interventions to treat choroidal neovascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Photodynamic therapy uses targeted laser activation of photosensitive dyes to selectively ablate or close choroidal vessels (SchmidtErfurth et al, 1999), and this therapy may soon be the standard of care for a limited group of ARMD patients. Small molecule inhibitors of angiogenesis are being developed to treat neovascular ARMD (Ishida et al, 1999;McNatt et al, 1999;Seo et al, 1999), and these may be useful for treating a larger population of patients in the future. The method of FITC-dextran labeling of CNV described in this study is reproducible and quanti®able, and it may accelerate the discovery of therapeutic interventions to treat choroidal neovascularization.…”
Section: Discussionmentioning
confidence: 99%
“…32,[35][36][37] Anecortave acetate exhibited the anti-angiogenic activity in both a rat model of retinopathy of prematurity and an intraocular tumor model. 38,39) It has also been reported that anecortave acetate is clinically efficacious for improving vision in patients with exudative AMD by the posterior juxtascleral administration (15 mg).…”
Section: Discussionmentioning
confidence: 99%
“…83 Rhen and Cidlowski 96 provide an in-depth discussion of events at the cellular level. The antiangiogenic effect of steroids is thought to result from multiple anti-inflammatory properties that include inhibition of cell chemotaxis, 84,85,92,97,98 modulation of the proteolytic activities of vascular endothelial cells that precedes the ''budding'' of new vessels, 20,75,92,99 inhibition of proinflammatory cytokines [tumor necrosis factor a, interleukin (IL) 1, and IL-6], 91,100-104 inhibition of plasminogen activator (PA) and/or stimulation of PA inhibitor activity or expression, 99 and prostaglandin (PG) (phospholipase A 2 via arachidonic acid release) 85,105 synthesis. Other effects include inhibition of vascular dilation, increased permeability of blood vessels to polymorphonuclear leukocytes, 106 stabilization of lysosomal membranes, 107 and destruction of lymphocytes.…”
Section: Steroidsmentioning
confidence: 99%